Two classical periodic problems on time scales - Amster, P. (2007)
We consider the generalization of two classical periodic problems to the context of time scales. On the one hand, we generalize a celebrated result by Castro for the forced pendulum equation. On the other hand, we extend a well-known result by Nirenberg to a resonant system of equations on time scales. Furthermore, the results are new even for classical difference equations. © 2007 Texas State University.